The Role of Airport Reputation And Subjective Well-Being In Mediating Environmentally Friendly Building Design on Passenger Behavioral Intention (A Study on Green Airport In Indonesia) - Danus Winarko; Sandriana Marina; Juliater Simarmata (Jurnal Ekonomi Manajemen Sistem Informasi, 2025)
Research on environmentally friendly building design has been widely conducted, including green decoration, living plants, environmentally friendly spaces, green atmospheres, but research that focuses on airports is still rare. This study aims to analyze the role of airport reputation and subjective well-being in mediating environmentally friendly building design on passenger behavioral intentions. The research method is quantitative. The sample used was 400 respondents who were passengers at Soekarno Hatta, I Gusti Ngurah Rai, Sultan Mahmud Badaruddin II, Juanda, Sultan Syarif Kasim II, and Sultan Hasanuddin airports. The sampling technique used accidental sampling. The data collection technique was a questionnaire. The data analysis technique used Structural Equation Modeling (SEM) based on Smart PLS. The results of the study showed that the environmentally friendly design of airport buildings directly influenced airport reputation, subjective well-being and behavioral intentions. Furthermore, airport reputation and subjective well-being influenced behavioral intentions, airport reputation and subjective well-being mediated the influence of environmentally friendly design of airport buildings on behavioral intentions. Researchers hope that airport managers will continue to improve environmentally friendly designs in airport buildings so as to create a reputation, subjective well-being, and behavioral intentions in users.